Design and Optimization Radial Gas Turbine Blade (Global Journals of Research in Engineering, 2013)
The combustion chamber of an automobile gasturbine engine can be designed to produce a gas temperature distribution at the inlet of the turbine increasing from blade root to blade tip. It is shown in the paper, by means of comparative calculations, that by using such distributions of temperatures blade life can be substantially increased, or else, un expensive materials can be used. Such gas temperature distributions produce non-isentropic flow conditions. It is developed in the paper a method for the aerodynamic design of blades within a non-isentropic flow and it is also shown that if the blades are designed by taking an average gas temperature, as it is usually made, important errors are introduced in the resulting shape of the blade, which reduces the efficiency of the turbine.